Considerations on knowledge, truth and ideas (1684) - von Leibniz, Gottfried Wilhelm; Másmela Arroyave, Carlos (Estudios de Filosofía, 1992)
The question concerning the truth and falsity of ideas is fervently treated today by illustrious men; and since Descartes himself has not found a satisfactory solution to this problem, which is of great significance for the knowledge of the truth. I would like to briefly expose my interpretation of the characteristic features and criteria of ideas and knowledge. Thus, knowledge is either dark or light; clear knowledge is either itself confusing or distinct; distinct knowledge is either inadequate or adequate; either symbolic or intuitive; ultimately, the most complete knowledge will be that which is both adequate and intuitive.